Data collection in the green patrol project - Kliček, Božidar (Naše gospodarstvo, 2007)
This article describes the methodology of a complex survey which uses multimodal delivery methods for data collection. Its general principle is how to reach all the needed profiles in a prompt manner and in different circumstances. This methodology is illustrated with the Green Patrol, an ecological project organized as a part of E!2584 Ulixes - Intelligent Tourist Organization project. This pilot project researches the present state of the environment and some environmental incidents as well. The Green Patrol project was performed in a local community of the town of Varazdin during a four week period at the end of the year 2004. Satisfaction with the present state and environmental protection was surveyed on-line, via SMS, and a paper survey questionnaire.
Keywords: naravne nesreče; podatki; zbiranje podatkov; metode; statistične metode; ankete